2005
DOI: 10.1158/1078-0432.ccr-05-0942
|View full text |Cite
|
Sign up to set email alerts
|

The −251T Allele of the Interleukin-8 Promoter Is Associated with Increased Risk of Gastric Carcinoma Featuring Diffuse-Type Histopathology in Chinese Population

Abstract: Purpose: Persistent interleukin-8 (IL-8) production contributes to chronic inflammation of the stomach. The proinflammatory IL-1h polymorphisms, which enhance the cytokine production, are associated with increased risk of gastric cancer. The À251A/T polymorphism of the IL-8 promoter is involved in several human diseases. Particularly, the À251A is associated with decreased risk of colorectal cancer. We aimed to determine whether the À251 allele resulting in high IL-8 expression was associated with increased ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
4
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 43 publications
3
100
4
3
Order By: Relevance
“…Our result for the overall GC risk was inconsistent with that from two other studies in Eastern and Southeastern China (Zeng et al, 2005), Northern China (Lu et al, 2005), and Chinese Taiwan (Lee et al, 2005); in former two studies, AA was suggested as a hazard genotype for GC, while TT rendered a risk in the Taiwan study. This indicates possible ORs and 95%CIs were calculated by conditional logistic regression and cOR stands for crude odds ratio.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our result for the overall GC risk was inconsistent with that from two other studies in Eastern and Southeastern China (Zeng et al, 2005), Northern China (Lu et al, 2005), and Chinese Taiwan (Lee et al, 2005); in former two studies, AA was suggested as a hazard genotype for GC, while TT rendered a risk in the Taiwan study. This indicates possible ORs and 95%CIs were calculated by conditional logistic regression and cOR stands for crude odds ratio.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, these studies adjusted different confounding factors (Lee et al, 2005) or apparently ignored potential confounding from lifestyle or environmental factors for overall analysis (Lu et al, 2005;Zeng et al, 2005), so the results might not be comparable to some extent.…”
Section: Gene Polymorphisms and Risk Of Gastric Cancer In A Populatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies also determined genetic polymorphisms in TNF-a and IL-10, which, when combined with proinflammatory IL-1β gene cluster polymorphisms, result in a high-risk genotype with a 27-fold or greater risk of developing gastric cancer (67). Studies have also identified the -251T allele in the IL-8 promoter as significantly associated with an increased risk of gastric cancer (68,69). These observations provide strong evidence for host genetics in determining progression to gastric cancer and strengthen the connection between the inflammatory response and the development of gastric atrophy.…”
Section: Host Factors That Affect the Development Of Gastric Cancer Gmentioning
confidence: 99%
“…Among individuals infected by H. pylori, ~1-2% may develop gastric cancer, including adenocarcinoma and mucosa-associated lymphoid tissue (MALT) lymphoma (3,6,7). Risk factors include the strain of H. pylori, the duration of the infection, host genetic polymorphisms, and diet or other environmental factors (8)(9)(10)(11)(12)(13). In cases with synchronous adenocarcinoma and lymphoma, H. pylori infection was present in 92% of the cases in Eastern countries and 68% of the cases in Western countries (14), although it remains rare for synchronous tumors.…”
Section: Discussionmentioning
confidence: 99%